DIGITALISASI DI KALANGAN GENERASI Z UNTUK PERKEMBANGAN EKONOMI BERBASIS SYARIAH - Romadi, Arsalan Bintang; Musyaffa, Muhammad Za’im; Saputra, Rega; Fauzi, Mustofa Mahfudz (Taksasila Edukasi Insani, 2024)
This study aims to analyze the potential of Generation Z as key actors in driving the growth of the Islamic economy through digitalization while enhancing their literacy regarding Islamic economic concepts and products. Using a literature review method and analytical opinions, this study explores the relationship between technological advancements and the role of Generation Z in expanding the reach of the Islamic economy. The findings reveal that Generation Z possesses unique characteristics, such as high proficiency in utilizing digital technology and a preference for products based on social and ethical values, which align with the principles of the Islamic economy. However, their literacy in this sector remains relatively low, necessitating creative and technology-based educational approaches. Additional challenges include limited access to user-friendly Sharia-compliant digital platforms and a lack of educational content tailored to their communication style. This study recommends synergy among governments, educational institutions, industry players, and digital communities to develop platforms and educational strategies that align with the needs of Generation Z. Proper implementation of Islamic economic digitalization could serve as a strategic solution for creating an inclusive, sustainable, and relevant economic system in the digital era.Keywords: Generation Z, Islamic economy, digitalization, Islamic economic literacy, digital technology, educational innovation.